Russian Language Learning Methods - Tursunova Inobat Mirkamilovna; Xashimova Feruza Uralovna (Zien Journals, 2022)
This article describes in detail the process and methods of teaching through the subject of the Russian language, the method of teaching the Russian language, the methods widely used in the methodology of teaching the Russian language and the relationship of methodology with didactics.
Keywords: methodology; didactics; method of communicative didactics; method of organizing exercises